Public procurement as a policy tool: using procurement to reach desired outcomes in society - Grandia, Jolien; Meehan, Joanne (The International journal of public sector management, 2017)
Purpose The purpose of this paper is to introduce the special issue and outline its major themes and challenges, their relevance and the research opportunities the field presents. Design/methodology/approach The paper reviews prior literature and outlines the need to view public procurement as a policy tool to introduce the contributions to this special issue. Findings Public procurement has been consistently used to further public policies in a wide range of fields. The collection of articles in this special issue contributes to a broader understanding of the role and potential of public procurement in delivering desired policy outcomes in society. The articles show that public procurement largely has strategic aspirations, and its potential to deliver on wider societal issues is attractive to policy makers. The issues raised in this collection of articles, however, also demonstrate that public procurement often lacks strategic maturity and critical issues, notably around how to demonstrate and evaluate its impact and “success”. Research limitations/implications This paper aims to stimulate interdisciplinary research into the role of public procurement as a policy tool and its ability to achieve public value. Originality/value This paper discusses theoretical and empirical findings that highlight the importance of public procurement for achieving public value. The special issue examines the interdisciplinary literature on public procurement and shows how it is being used to achieve public value.